Custom shirts and printing design / Muhammad Syazwi Razin Ridzahudin - Muhammad Syazwi Razin, Ridzahudin (2020)
Two Hundred Percent was inspired by my mom’s scarf business, I wanted to have a great and successful business like her. By having this kind of business is always been my dreams since I was a child. I really wanted to have my own brand and introduce it to the world. Seeing how my mom’s business brings great profit, I am inspired to work hard and follow her footsteps but with my own concept of business ideas. Two Hundred Percent is a local shirt retailer that is located at Central I-City Mall, Selangor. Since my target market is among the teenagers, Central I-City Mall is the most suitable places for my business as it is the places for the teenagers to hang out and shop for branded shirts. Furthermore, having a shop at a mall will make my business brand looks fancy and exclusive. The main purpose of Two Hundred Percent is to show the uniqueness of material used in my products where it is high in quality. By using Supima cotton in our product, it is beneficial for the customers as it is the best material for shirts which are high in quality and comfortable to be wear everywhere at any time. Plus, due to high demand on the trend of fashion these days especially among adolescent that always up to date in any new trendy designs, my t-shirt updated with any trend and fashion in a modern way to suit the trends. Customers that interested in printing their own designs, they can take orders and my staff will print it the way they wanted. Other than that, this business is a one way to promote local t-shirt printing brand to the foreigner and help to increase gross domestic product to economic country. By maintaining to give good services and keep up the quality of my products, I believe my small business of local brand could be one of the best competitors among the famous brand like Zara and Top Shop. This business plan is made to give full view and perspectives in running this type of business.